Ex.3. If a + b + c = 2s, then (s-a)...
Question
Fullscreen

Ex.3. If a + b + c = 2s, then (s-a)²+(s – b)² +(s-c)² +52 al + b2 +c2 (1) a² +b +2 (2) 0 (3) 1 (4) 2 is equal to

11th - 12th Class
Maths
Solution
116
Rating
4.0 (1 ratings)
Fullscreen
sol. (3) Expression [ begin{array}{c} frac{(s-a)^{2}+(s-b)^{2}+(s-c)^{2}+s^{2}}{a^{2}+b^{2}+c^{2}} =frac{s^{2}-2 s a+a^{2}+s^{2}+b^{2}-2 b s+s^{2}+c^{2}-2 c s+s^{2}}{a^{2}+b^{2}+c^{2}} =frac{4 s^{2}+a^{2}+b^{2}+c^{2}-2 s(a+b+c)}{a^{2}+b^{2}+c^{2}} =frac{4 s^{2}+a^{2}+b^{2}+c^{2}-4 s^{2}}{a^{2}+b^{2}+c^{2}}=1 end{array} ]
Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free